2019
DOI: 10.5009/gnl18278
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Can Reduce the Risk of Gallstone Disease: A Systematic Review with a Dose-Response Meta-Analysis of Case-Control and Cohort Studies

Abstract: Background/AimsGallstone disease (GSD) is a common gastrointestinal disorder. Clinical epidemiological studies revealed that alcohol consumption has a preventive effect on the development of GSD. This study aimed to evaluate the relative risks of drinking for GSD development and investigate the dose-response relationships.MethodsA systematic search of the MEDLINE, EMBASE, and Cochrane Library databases for studies published up to 2018 was performed. All studies that satisfied the following eligibility criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 46 publications
(39 reference statements)
1
10
0
1
Order By: Relevance
“…To date, evidence linking alcohol drinking with GSD is controversial ( 9 ). In this meta-analysis, we verify a negatively non-linear dose–response association between drinking alcohol grams per day and GSD risk, consistent with Cha et al ( 34 ), but the strict study design and dose definition are used in our study. We conclude that the association of GSD risk reduction appears to reach the limit when the dose is higher than 45 g/day, and this finding (J-shaped) is similar to that of Figueiredo et al ( 5 ), while the appropriate dose of alcohol-intake protects against GSD awaits future study.…”
Section: Discussionsupporting
confidence: 90%
“…To date, evidence linking alcohol drinking with GSD is controversial ( 9 ). In this meta-analysis, we verify a negatively non-linear dose–response association between drinking alcohol grams per day and GSD risk, consistent with Cha et al ( 34 ), but the strict study design and dose definition are used in our study. We conclude that the association of GSD risk reduction appears to reach the limit when the dose is higher than 45 g/day, and this finding (J-shaped) is similar to that of Figueiredo et al ( 5 ), while the appropriate dose of alcohol-intake protects against GSD awaits future study.…”
Section: Discussionsupporting
confidence: 90%
“…However, we cannot rule out the causal relationship between them, as a weak nonlinear relationship was reported. [ 46 ] Furthermore, nonlinear MR analysis should be carried out to explain it.…”
Section: Discussionmentioning
confidence: 99%
“…As for cholecystolithiasis or gallbladder disease, although drinking is a risk factor for biliary cancers, Byung et al [ 38 ]. found that drinking can reduce the risk of cholecystolithiasis by 16% (RR = 0.84, 95% CI = 0.79–0.89).…”
Section: Resultsmentioning
confidence: 99%